BUSINESS MODEL INNOVATION: DIFFERENT APPROACHES, OPPORTUNITIES AND CHALLENGES CASE STUDY OF AIRBNB IN HOTEL BUSINESS - LE, TRANG (My University, 2020)
Aim: The master thesis “Business Model Innovation: Different Approaches, Opportunities and Challenges” aims to explore business model innovation, opportunities and challenges from implementing these innovative changes especially in hotel business via the case study of Airbnb. To simply summarize, this thesis studies business model innovation in hotel business. Framework: The thesis studies business model (BM), business model innovation (BMI) literature, process to develop a BMI with more emphasis on opportunities and challenges of BMI implementation. The literature about business model innovation includes an illustration of a three-phase development process of a BMI whose last phase with opportunities and challenges is further emphasized. The created model is then applied to analyze findings in empirical part, ensures the tight connection between findings and literature review. Methodology: The theoretical development of this thesis is completed with an abductive approach. The empirical section is a single case-study from hotel business. The material was collected via semi-structured interviews with people who acquire related understanding of the case. The idea generated from this thesis is under both subjective and interpretative approach. Findings and contribution: The application of business model innovation in hotel business was found to be surprisingly similar with the case. BMI was generated from accidental/purposed changes or modifications in already-existing model. Opportunities and challenges were defined according to the implementation of new changes. Generally, the findings highlight the importance of understanding existing models to figure out key components for modification because BMI is started from this change.
Keywords: business models; business; enterprises; tourist services; strategic planning; entrepreneurship; accommodation sector; tourism businesses; hotel sector; business ideas; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development